Relationships Among Trophic Niche Width, Morphological Variation, and Genetic Diversity of Hemiculter leucisculus in China - Li, Wenjing; Zhai, Dongdong; Wang, Chunling; Gao, Xin; Liu, Huanzhang; Cao, Wenxuan (Frontiers in Ecology and Evolution, 2021)
According to the niche variation hypothesis (NVH), the populations with wider niches are phenotypically more variable than those with narrow niches. Giller (1984) expanded the NVH, suggesting that the niche width, morphological variation, and genetic diversity are all positively correlated. However, the hypothesis has been a subject of debate and discussion. In the present study, the NVH was tested by analyzing the relationships among trophic niche width, morphological variation, and genetic diversity of Hemiculter leucisculus, a widespread cyprinid fish. The fish samples were collected from six sites across Haihe, the Yellow, and the Yangtze River basins in China. The relationships among trophic niche width, morphological variation, and genetic diversity were analyzed using Pearson correlation at the inter-population level. Our analysis indicated that trophic niche width is significantly positively correlated with morphological variation, which corroborates the NVH. Morphological variation was significantly correlated to genetic diversity. However, no relationship was observed between trophic niche width and genetic diversity. We inferred that the dietary niche of H. leucisculus might change due to the plastic response towards environmental changes rather than due to the genetic variation. We also suggest that the effects of environment and heredity on the niche of the freshwater fish should be quantified separately in further studies.